A Proposed Vision for Using Artificial Intelligence in Enhancing Strategic Value of Human Resources - Nadera Hourani (International Journal of Industrial Engineering and Production Research)
Artificial intelligence (AI) has been integrated into human resource management (HRM), enabling the transformation of the field through routine job automation, decision-making enhancement, and evidence-based strategies. This article will systematically review the role of AI in HRM, focusing on applications related to recruitment, employee engagement, workforce planning, and retention. This systematic review article underlines the significant benefits of AI adoption by analyzing ten peer-reviewed studies using advanced statistical analysis. These benefits include efficiency gains, increased employee satisfaction, and strategic workforce optimization. Yet, there are significant challenges in the form of algorithmic bias, data privacy concerns, and organizational readiness. Regression and correlation analyses show a strong positive relationship between AI use and HR performance metrics, with a greater effect on recruitment and retention. Though AI has a huge potential for transformation, the findings have brought into focus the need for ethical guidelines, strong data protection, and employee upskilling for the full realization of AI's capabilities in HRM. Thus, this study provides practical insights for organizations seeking to adopt AI technologies while addressing the associated challenges.